Quality Assessment of Widal Test in Microbiology Laboratories at Primary and Secondary Level Before and After Implementation of Standard Operating Procedure (SOP): A Comparative Study (Journal of Dhaka Medical College, 2015)
Context: The use of standard operating procedures (SOP) in laboratory testing is one of the most crucial factors in achieving the quality. In primary and secondary level laboratory, the scope for microbiological test is limited. Enteric fever is one of the major public health problem in the developing countries, including Bangladesh. An undiagnosed and maltreated case of enteric fever may result in serious complication and even prove fatal. Widal test is the very extensively used serological test in laboratory at all level to aid in the diagnosis of enteric fever. It is the only available practical test for demonstrating antibodies to Salmonella typhi and S. paratyphi. In this study, an attempt has been made to evaluate the present status of microbiology laboratory by comparing the test results of investigator with that of laboratory staff for widal test at primary and secondary level before and after implementation of standard operating procedure (SOP) .Methods: The present study was performed on clinically suspected cases of enteric fever attending at the primary and secondary level laboratories for widal test. A 120 blood samples were collected before implementing SOP and 50 blood samples were collected and tested after following SOP. A cross sectional, descriptive type of study was conducted in Narsingdi Sador Hospital as secondary level microbiology laboratory and Polash Upzilla Health Complex as primary level microbiology laboratoryResults: Before standard operating procedures (SOP), significant titre of widal test was found more by the investigator than the staff at both primary and secondary level. This difference in results was statistically significant (p0.05).Conclusion: Implementing SOP for widal test and after practicing appropriate and standard techniques for dilution of serum at primary and secondary level, discrepancy in the results of widal test between investigator and staff was reduced and overall quality of tests were improved.J Dhaka Medical College, Vol. 23, No.2, October, 2014, Page 227-233